Answer:
Nope the answer would be -6.5
Let width of rectangle be "x"
L= 3x W=x
if width is diminished by 1 that means new width = (x-1)
similarly the new length would be (3x+3)
hence (x-1)*(3x+3)=72
(3x^2)-3=72
3x^2=75
x^2=25
x= +/- 5
reject -5 as you cant have negative length
hence x=5
so original dimensions of rectangle is
L= 15m W=5m
Answer:
6
Step-by-step explanation:
Given
![\frac{8}{-4} / \frac{-3}{9}](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B-4%7D%20%2F%20%20%5Cfrac%7B-3%7D%7B9%7D)
Required
Solve
![\frac{8}{-4} / \frac{-3}{9}](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B-4%7D%20%2F%20%20%5Cfrac%7B-3%7D%7B9%7D)
We start by converting the division sign to multiplication
![\frac{8}{-4} / \frac{-3}{9} =\frac{8}{-4} * \frac{-9}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B-4%7D%20%2F%20%20%5Cfrac%7B-3%7D%7B9%7D%20%3D%5Cfrac%7B8%7D%7B-4%7D%20%2A%20%20%5Cfrac%7B-9%7D%7B3%7D)
Then, we divide -9 by 3
Then, we divide 8 by -4
Multiply -2 and -3 to give final result
![\frac{8}{-4} / \frac{-3}{9} = 6](https://tex.z-dn.net/?f=%5Cfrac%7B8%7D%7B-4%7D%20%2F%20%20%5Cfrac%7B-3%7D%7B9%7D%20%3D%206)
Hence,
is equivalent to 6
Answer:
Second option: (-2,-3) and (1,0)
Step-by-step explanation:
Given the system of equations
, you can rewrite them in this form:
![x^2 + 2x-3= x - 1](https://tex.z-dn.net/?f=x%5E2%20%2B%202x-3%3D%20x%20-%201)
Simplify:
Factor the quadratic equation. Choose two number whose sum be 1 and whose product be -2. These are: 2 and -1, then:
![(x+2)(x-1)=0\\\\x_1=-2\\\\x_2=1](https://tex.z-dn.net/?f=%28x%2B2%29%28x-1%29%3D0%5C%5C%5C%5Cx_1%3D-2%5C%5C%5C%5Cx_2%3D1)
Substitute each value of "x" into any of the original equation to find the values of "y":
![y_1= (-2) - 1=-3\\\\y_2=(1)-1=0](https://tex.z-dn.net/?f=y_1%3D%20%28-2%29%20-%201%3D-3%5C%5C%5C%5Cy_2%3D%281%29-1%3D0)
Then, the solutions are:
(-2,-3) and (1,0)
The original side length was 12m therefore the perimeter was 36m. 12/4 is 3 so the perimeter is now 9, and the difference between them is 27.